Analisis Wacana dan Representasi Perempuan Dalam Media Merdeka.com : (Kajian Awk Van Leeuween dan Sara Mills) - Rahmat Sulo (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2023)
RAHMAT SULO. 2023. Discourse Strategy and Representation of Women's Reporting in News Headlines on Media.com: Critical Discourse Analysis Study (Supervised by Lukman and Ery Iswary) This research is a qualitative research that analyzes how the discourse strategy of the AWK Van Leewen model (inclusion and exclusion) is used in women's reporting on the merdeka.com news headline and how the representation of women's news on the Merdeka.com news headline uses the AWK Sara Mills model (subjects-objects). and reader-writer position). The data source for this research was found in news headlines on the Merdeka.com media. The population of this study amounted to 100 data. The data sample was selected purposively. The data collection technique used in this study was library research in the form of observation techniques, note-taking techniques and screenshot techniques. The data analysis technique used in this study is to analyze Van Leewen's discourse strategy (inclusion and exclusion) in women's news headlines on Merdeka.com and to analyze the representation of women's news in Merdeka.com news headlines using the AWK Sara Mills model. the method used in this research is descriptive method. The results of this study indicate that there are three types of exclusionary discourse strategies used by Merdeka.com media in reporting on women, namely a) passivation, b) nominalization, and c) substitution of clauses. In addition, the results of this study also show that there are 7 types of inclusion discourse strategies used by Merdeka.com media, namely a) differentiation-indifference, b) objectivation-abstraction, c)nomination-categorization, d)nomination-identification, e)assimilation-individualization, and f) associations-disassociations. In this case Merdeka.com media tends to protect the suspect (male) by eliminating the perpetrator in the news text title. On the other hand, representation according to Sara Mills' AWK model is divided into two parts, namely: a) based on the point of view of the subject-object and b) based on the point of view of the writer (media) - the point of view of the reader (researcher). In this case the representation of women's news in the Merdeka.com news headlines tends to make women the object of the news, causing women to consume the text in Merdeka.com's news titles. Keywords: Discourse Strategy, Representation, and News Titles.